Protein ontology - Sidhu, Amandeep; Dillon, Tharam S.; Chang, Elizabeth (Artech House, 2007)
Two factors dominate current developments in structural bioinformatics, especially in protein informatics and related areas: (1) the amount of raw data is increasing, very rapidly; and (2) successful application of data to biomedical research requires carefully and continuously curated and accurately annotated protein databanks. In this chapter, we introduce the concepts for annotating protein data using our protein ontology. We first describe and review existing approaches for protein annotation.We then describe the advantages of semantic integration of protein data using Web ontology language, in comparison to annotating using automatic search and analyzing using text mining. The rest of chapter is devoted to the use of the protein ontology for the annotation of protein databases. The protein ontology is available at http://www.proteinontology.info/.